KETOPRAK LESUNG “ CAHYO BUDOYO “ DI DUSUN SIDOWAYAH, HARGOWILIS, KOKAP, KULON PROGO ( SUATU TINJAUAN ASPEK SOSIAL BUDAYA ) - Salim Salim (Canthing, 2014)
Form of art has a function for society in accordance with the natural conditions and the state of social culture where art is born. Sidowayah village communities living in areas far from urban centers or entertainment, with the background of the people whose livelihood as farmers cocoa and palm tapper majority of senior high school education, have some traditional art forms, one of which is Ketoprak Dimples "Cahyo Budoyo".Ketoprak Dimples "Cahyo Budoyo" the hamlet community Sidowayah serve to foster the reciprocal relationship between the two. Ketoprak Dimples "Cahyo Budoyo" as a result of artistic expression Sidowayah village community as one of the traditional arts in the community Sidowayanh hamlet. Because Ketoprak Dimples "Cahyo Budoyo" is communally owned village Sidowayah of society, in which people actively participate directly involved to preserve what they have. Sidowayah village communities who live far away from the hustle of the city requires art or even entertainment that can provide useful information for them. Ketoprak Dimples "Cahyo Budoyo" is a reflection of the life of the village community. This art reveals the existence of communal solidarity, simplicity, and a democratic society in the spirit of his supporters.